2020
DOI: 10.1099/ijsem.0.004332
|View full text |Cite
|
Sign up to set email alerts
|

List of Prokaryotic names with Standing in Nomenclature (LPSN) moves to the DSMZ

Abstract: The List of Prokaryotic names with Standing in Nomenclature (LPSN) was acquired in November 2019 by the DSMZ and was relaunched using an entirely new production system in February 2020. This article describes in detail the structure of the new site, navigation, page layout, search facilities and new features.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
949
0
13

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,297 publications
(966 citation statements)
references
References 7 publications
4
949
0
13
Order By: Relevance
“…We obtained descriptions for 7,021 species, yet the total number of species validly published in the literature is 20,038 [see ref. (18)]. In total, our results suggest that databases reporting metabolic traits are far less than 1/4 complete.…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…We obtained descriptions for 7,021 species, yet the total number of species validly published in the literature is 20,038 [see ref. (18)]. In total, our results suggest that databases reporting metabolic traits are far less than 1/4 complete.…”
Section: Resultsmentioning
confidence: 75%
“…We need to explore, first, sources of species descriptions other than Bergey’s Manual. Though Bergey’s Manual gave us descriptions for over 7,000 species, this represents only ~1/3 of all species validly published in the literature (18). We need to explore, second, well our methods work with rare traits.…”
Section: Discussionmentioning
confidence: 99%
“…proposed to merge the two genera based on the up-to-date phylogenomic evidence and similar phenotypic characteristics among the type strains [3]. As of October 2020, the genus Roseibium comprises 11 species with validly published names, which can be found in the updated LPSN website (https://lpsn.dsmz.de/genus/roseibium) [4]. The other two species, Labrenzia polysiphoniae [5, 6] and ‘ Labrenzia callyspongiae ’ [7] (the name of the latter is effectively but not yet validly published and thus is in quotation marks throughout this study), have not been emended, probably due to the proposal of these two species later than the beginning of Hördt’s study [3], and thus the taxonomic status of the two species remains to be confirmed.…”
Section: Full-textmentioning
confidence: 99%
“…At the time of writing, the genus encompasses 25 validly published species [9]. The species ‘ Glycomyces tritici ’ by Li et al [10], ‘ Glycomyces luteolus ’ by Duan et al [11] and ‘ Glycomyces xinjiangensis ’ by Guan et al [12] also have been described recently but the names are not yet validly published.…”
Section: Full-textmentioning
confidence: 99%